Strategic environmental assessment of the Docklands master plan - Prendergast, Terry (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2004)
Directive 2001142/EC of the European Parliament and Council on Strategic Environmental Assessment or SEA, which entered into force on 21 July 2001 , requires Member States to assess the likely significant environmental effects of plans and programmes prior to their adoption, thus providing for the assessment of strategic environmental considerations at an early stage of the decision-making process. The Department of the Environment, Heritage and Local Government approached the Dublin Docklands Development Authority (the Authority) in June 2002 as it considered the Docklands Area to be an appropriate area to pilot test SEA on a non-statutory basis in tandem with the review of the 1997 Master Plan. It was anticipated that the experience gained by the Dublin Docklands Development Authority in piloting SEA would provide an input to the proposed guidelines for planning authorities on SEA which the Department intended drawing up as part of the process of the general implementation of the Directive. The carrying out of the SEA proved to be an invaluable learning process for those involved and this paper seeks to share the lessons gained from the experience.
Papers from practice
Keywords: Urban geography -- Ireland